Drying characteristic of Carica papaya L. during microwave vacuum treatment - Muhamad, Ida Idayu; Md. Zaki, Nurul Asyikin; Md. Salleh, Liza (2007)
Microwave vacuum drying is of increased interest among food researchers. The microwave power and system pressure plays an important part to ensure that the product quality is improved. The aim of this project is to study the effect of power intensities and system pressures during microwave dehydration on drying characteristics of Carica papaya L. Samples of papaya were treated in microwave vacuum drying equipment at different power levels (110, 380 and 750 W) and pressures (200, 450 and 700 mmHg) to achieve 80% reduction of moisture content. The drying rate increased with increasing power intensity and system pressure at the same moisture content. Higher microwave power level and system pressure resulted in shorter drying time.